2014
DOI: 10.1016/j.bjane.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pacemakers and implantable cardioverter defibrillators – general and anesthetic considerations

Abstract: A pacemaking system consists of an impulse generator and lead or leads to carry the electrical impulse to the patient's heart. Pacemaker and implantable cardioverter defibrillator codes were made to describe the type of pacemaker or implantable cardioverter defibrillator implanted. Indications for pacing and implantable cardioverter defibrillator implantation were given by the American College of Cardiologists. Certain pacemakers have magnet-operated reed switches incorporated; however, magnet application can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Anatomically, the near-surface implantable devices are implanted in between the dermis and subcutaneous layer of the skin [2,3,17]. The dermis layer, as shown in Fig.…”
Section: Animal Tissuementioning
confidence: 99%
“…Anatomically, the near-surface implantable devices are implanted in between the dermis and subcutaneous layer of the skin [2,3,17]. The dermis layer, as shown in Fig.…”
Section: Animal Tissuementioning
confidence: 99%
“…Implantable cardioverter defibrillator (ICD) detects ventricular tachycardia (VT) and ventricular fibrillation (VF) and delivers therapy in the form of overdrive antitachycardia pacing (ATP), low-energy cardioversion, and high-energy defibrillation 1 . It is indicated for patients at high risk for malignant ventricular tachyarrhythmias (primary prophylaxis) and in patients who have survived from a malignant ventricular tachycardia (secondary prophylaxis) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that electrosurgical units are most common form of electromagnetic interference (EMI) in the operating room (OR). [ 2 3 ]…”
mentioning
confidence: 99%
“…EMI from electrocautery can result in pulse generator inhibition or component failure, atrial or ventricular tachycardia and fibrillation, loss of/change in output, reprogramming of rate or mode of function, runaway pacing and electrical burns at the myocardial-electrode interface. [ 2 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation